Highly Efficient MoS2/CsxWO3 Nanocomposite Hydrogen Gas Sensors - Wu, Chang-Mou; Shrisha,; Motora, Kebena Gebeyehu; Chen, Guan-Ying; Kuo, Dong-Hau; Gultom, Noto Susanto (Frontiers in Materials, 2022)
Hydrogen gas sensors are important because of the significant use of hydrogen in industrial and commercial applications. In this study, we synthesized a novel CsxWO3/MoS2 nanocomposite using a solvothermal method. The samples were spin-coated on Si/SiO2 substrates, and the sensors were fabricated with interdigital electrodes. The hydrogen gas sensing properties of the sensor were investigated. CsxWO3/MoS2 exhibited an outstanding hydrogen gas sensing ability at room temperature. In particular, the nanocomposite comprising 15 wt.% MoS2 (15 % CsxWO3/MoS2) showed a 51 % response to hydrogen gas at room temperature. Further, it exhibited an excellent cyclic stability for hydrogen gas sensing, which is crucial for practical applications. Therefore, this study facilitates the development of effective and efficient hydrogen gas sensors operable at room temperature.